Marketing político para elecciones del Estado de Michoacán - Ochoa Barajas, Luis Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
Next the 11 of November of the 2007, in the State of Michoacán de Ocampo will choose 40 Deputies to the Congress of the State, of which 24 will be elect by the route of the representative majority and the rest by proportional representation, As the 113 respective Mayors and Receivers and their regidores for he himself I number of municipalities, as well as the election of Governor, all of them by a lapse of four years. The diverse political parties receive financing I publish for the accomplishment of their campaigns in reason to the proportion of votes obtained in the previous elections, reason why it is necessary to determine whereupon started off or divided politicians he is advisable in monetary and political terms to make an alliance. The strong parties but in the state are: Institutional Revolutionary party (PRI), Divided of Revolution Democratic (PRD) and Party National Action (BREAD), and exists others Like in Green Ecologist of Mexico (PVEM), Started off of Trabajo (PT) and Divided of Social Convergence (PCS), so that the three first will be able to determine whereupon started off to make an alliance to be able to obtain the electoral triumph the next Sunday 11 of November. The Party Convergence is a party that in diverse states as in this own this in increasing form, therefore it is considered that it is the one who can contribute but politically and it is like second to contribute in the financial aspect, reason why considering that is a left party net, the Party of the Democratic Revolution will be able to arrive at solio of Ocampo in a possible alliance. Considering which the Party of the Work is one of which they have a good financing I publish for the electoral processes, reason why is extremely attractive.

El próximo 11 de Noviembre del 2007, en el Estado de Michoacán de Ocampo se elegirán 40 Diputados al Congreso del Estado, de los cuales 24 serán electos por la vía de la mayoría representativa y el resto por representación proporcional, Como los 113 Alcaldes y Síndicos y sus regidores respectivos para el mismo número de municipios, así como la elección de Gobernador, todos ellos por un lapso de cuatro años. Los diversos partidos políticos reciben financiamiento público para la realización de sus campañas en razón a la proporción de votos obtenidos en las elecciones anteriores, por lo que es necesario determinar con qué partido o partidos políticos es conveniente en términos monetarios y políticos realizar una alianza. Los partidos más fuertes en el estado son: Partido Revolucionario Institucional (PRI), Partido de la Revolución Democrática (PRD) y Partido Acción Nacional (PAN), y existen otros Como en Verde Ecologista de México (PVEM), Partido del Trabajo (PT) y Partido de Convergencia Social (PCS), porque los tres primeros podrán determinar con qué partido realizar una alianza para poder obtener el triunfo electoral el próximo domingo 11 de Noviembre. El Partido Convergencia es un partido que en diversos estados como en este propio esta en forma creciente, por lo tanto se considera que es quien puede aportar más políticamente y se encuentra como segundo para aportar en la aspecto financiero, por lo que considerando que es un partido netamente de izquierda, el Partido de la Revolución Democrática podrá llegar al solio de Ocampo en una posible alianza. Considerando que el Partido del Trabajo es uno de los que tienen un buen financiamiento público para los procesos electorales, por lo que es sumamente atractivo.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2007-0065; Mercadotecnia; Política; Electoral; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5855